INVESTIGATION AND DEVELOPMENT OF CONSUMER PROPERTIES OF BALSAM BASED ON LOCAL RAW MATERIALS - Popova D.G.; Titorenko E.Y.; Poznyakovskiy V.M. (Техника и технология пищевых производств, 2015)
One of the priorities of the state policy in the field of prevention of nutrition-related diseases and health pro-motion is the solution of problems of food safety, as well as the formation of scientific bases and the industry of healthy nutrition. The main direction of the problem is the development and practical implementation of new types of specialized products with various functions. This way proves to be the most efficient and economically rational as well as acknowledged at the state level by the Decrees of President and Resolutions of the Government of the Russian Federation. One of the objects under consideration can be non-alcoholic beverages, in particular balsams, taking into consideration their popularity and demand among the population. All these considerations have determined the purpose and objectives of the present research. The purpose of this research is to investigate and develop consumer properties of a new balsam based on local raw materials. The objects of the study were the samples of non-alcoholic balsams based on sugar syrup, composition components and production technologies. Conventional and special research methods were used during the assessment of the product quality. The recipe for the enriched non-alcoholic balsam that includes functional bioactive substances has been formulated. The functional aim of the "Golden lake" balsam is defined by the following ingredients: extract of cinnamon rose (Rosa majalis Herrm), extract of rowanberry (Sorbus aucuparia Shneid.), extract of Rhodiola rosea (Golden root) (Rhodiola rosea L.), pantohematogen-S and blackcurrant juice (Ribes nigrum L.). The production technology of a new product has been developed and tested. It consists of the following stages: raw material preparation, balsam manufacture, filling and packing. Regulated organoleptic and physical and chemical properties of a new product have been defined. Energy and nutritional values have been calculated: 100 ml of the balsam contain 60 g of carbohydrates and no less than 110 mg of vitamin C. The energy value is 240 kcal. The terms and conditions of product storage have been determined. The technical documentation for the new product has been developed. The developed balsam is recommended as a supplementary source of vitamin C with direct functional properties.